Investigation of Online Learning Satisfaction During COVID 19: In Relation to Academic Achievement - Abd Basith; Rosmaiyadi Rosmaiyadi; Susan Neni Triani; Fitri Fitri (Journal of Educational Science and Technology (EST), 2020)
The aim of this research is; 1) investigating the level of online learning satisfaction among students during COVID 19; 2) analyzing the influence of differences in gender, years of study, major in determining online learning satisfaction among students during COVID 19; 3) to analyze the relationship between online learning satisfaction and student academic achievement during COVID 19. The population was 656 students at STKIP Singkawang, and then a sample of 357 students (87 males and 270 females) was taken using a simple random sampling technique. The instrument in this study was adapted from Aman's Satisfaction instrument, which was then used to collect research data. Data analysis using SPSS with descriptive statistical techniques, MANOVA, and correlation. The results showed that online learning satisfaction was at a high level, meaning that students were satisfied with the online learning that had been implemented. The major differences have a significant effect on determining online learning satisfaction. Intercorrelation shows that there is a significant relationship on each indicator of online learning satisfaction with academic achievement, meaning that the higher the satisfaction felt by students in online learning, the student's academic achievement will increase.